2016
DOI: 10.1007/s40090-016-0108-6
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic degradation of tetracycline aqueous solutions by nanospherical α-Fe2O3 supported on 12-tungstosilicic acid as catalyst: using full factorial experimental design

Abstract: In this paper, spherical a-Fe 2 O 3 nanoparticles (NPs) were supported on the surface of 12-tungstosilicic acid (12-TSAÁ7H 2 O) using two different solid-state dispersion (SSD) and forced hydrolysis and reflux condensation (FHRC) methods. Photocatalytic activity of supported a-Fe 2 O 3 NPs (a-Fe 2 O 3 /12-TSAÁ7H 2 O) for tetracycline (TC) degradation in aqueous solution was investigated using UV/H 2 O 2 process and the results were compared with that of pure a-Fe 2 O 3 NPs. a-Fe 2 O 3 and 12-TSAÁ7H 2 O were sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 50 publications
(51 reference statements)
0
12
0
Order By: Relevance
“…Compared to the green and red light, blue light excitation provided the highest efficacy of TC degradation. To decompose TC from water, a heavy metal-based catalyst, such as TiO 2 [ 35 , 36 ], SrTiO 3 [ 37 ], ZnO [ 38 ], Fe 2 O 3 [ 39 ], and Fe 2+ or Fe 3+ /H 2 O 2 [ 40 ], are usually added and activated with UV radiation. However, heavy metals and UV radiation are hazardous to the environment and animals.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to the green and red light, blue light excitation provided the highest efficacy of TC degradation. To decompose TC from water, a heavy metal-based catalyst, such as TiO 2 [ 35 , 36 ], SrTiO 3 [ 37 ], ZnO [ 38 ], Fe 2 O 3 [ 39 ], and Fe 2+ or Fe 3+ /H 2 O 2 [ 40 ], are usually added and activated with UV radiation. However, heavy metals and UV radiation are hazardous to the environment and animals.…”
Section: Discussionmentioning
confidence: 99%
“…The analysis of variance provides a statistical process that determines the means of several groups are equal or not. F value is used to test the significance of the model, individual variables and their interactions [29,30]. The p value is used to check the significance of the coefficient and p value < 0.05 shows that the model is significant and higher than 5% model is not significant.…”
Section: Accuracy Of the Modelmentioning
confidence: 99%
“…In this study, for degradation of dye as dangerous pollutants used a photoreactor with capacity 0.5 L that shows the schematic diagram in Fig.1. The photodegradation process using full factorial experimental design was studied by many investigators (18)(19)(20). The maximum photodegradation efficiency of AR14 obtained in this study was found to be 90.65%, corresponding to the operating conditions of 3, 30 mg L -1 and 20 ppm respectively, for the pH, catalyst amount and H 2 O 2 concentration.…”
Section: The Statistical Analysismentioning
confidence: 63%